2001
DOI: 10.1029/2000tc900027
|View full text |Cite
|
Sign up to set email alerts
|

Alpine structural and metamorphic signature of the Sila Piccola Massif nappe stack (Calabria, Italy): Insights for the tectonic evolution of the Calabrian Arc

Abstract: . The revised structural and metamorphic scenario is here integrated into a new tectonic evolutionary reconstruction, which involves an early high-P/low-T top to the east crustal thickening episode during the construction of the Apennine orogenic wedge (Eocene-Oligocene), followed and overprinted by a top to the west extensional shear, probably active from the !ate Oligocene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
116
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(120 citation statements)
references
References 45 publications
4
116
0
Order By: Relevance
“…It should be noted that the sequence described here generally agrees with the classic picture of Amodio-Morelli et al (1976), which fi t our fi eld observations better than does the reinterpretation of Rossetti et al (2001Rossetti et al ( , 2004.…”
Section: Regional Geology Of Northern Calabriasupporting
confidence: 90%
“…It should be noted that the sequence described here generally agrees with the classic picture of Amodio-Morelli et al (1976), which fi t our fi eld observations better than does the reinterpretation of Rossetti et al (2001Rossetti et al ( , 2004.…”
Section: Regional Geology Of Northern Calabriasupporting
confidence: 90%
“…By analyzing the polarity of fault arrays in relation to regional detachment faults, Stewart and Argent (2000) concluded that the presence of an underlying detachment clearly favors fault systems, which are synthetic to the underlying detachment. If these conclusions are applied here, the geometry of the early stages of rifting in Calabria was controlled by regional, ductile-to-brittle, top-tothe-W simple shear extension, which has been previously recognized as responsible for attenuation of the orogenic crustal section (Rossetti et al, 2001.…”
Section: Structural Architecture Of the Crati Basinmentioning
confidence: 98%
“…The causes of the fi rst cooling phase have been extensively discussed Wallis et al, 1993;Messina et al, 1996;Bonardi et al, 2001;Rossetti et al, 2001;Iannace et al, 2007), while causes and mechanisms of the second one have never been investigated.…”
Section: Introductionmentioning
confidence: 99%